2018
DOI: 10.5296/ajfa.v10i1.13282
|View full text |Cite
|
Sign up to set email alerts
|

Real Earnings Management: A Review of Literature and Future Research

Abstract: In recent years, increasing attention has been given to real earnings management (REM) as an alternative method to accrual-based earnings management. This paper reviews the recent studies on REM to provide updated and comprehensive information about this type of earnings management. Specifically, the review focuses on REM definitions, motivations, techniques, consequences, and measurement. In addition, the paper provides a discussion of the theoretical frameworks used by researchers as underpinning theories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 48 publications
1
20
0
2
Order By: Relevance
“…The earnings management literature reports several techniques used by company managers to affect reported earnings. These techniques are considered to be key indicators of earnings quality and consequently financial reporting quality (Ali and Kamardin, 2018b;Jeong and Choi, 2019). Earnings management is defined severally in the literature, but a comprehensive definition was introduced by Healy and Wahlen (1999): "Earnings management occurs when managers use judgment in financial reporting and in structuring transactions to alter financial reports to either mislead some stakeholders about the underlying economic performance of the company or to influence contractual outcomes that depend on reported accounting numbers" (p. 368).…”
Section: Real Earnings Managementmentioning
confidence: 99%
“…The earnings management literature reports several techniques used by company managers to affect reported earnings. These techniques are considered to be key indicators of earnings quality and consequently financial reporting quality (Ali and Kamardin, 2018b;Jeong and Choi, 2019). Earnings management is defined severally in the literature, but a comprehensive definition was introduced by Healy and Wahlen (1999): "Earnings management occurs when managers use judgment in financial reporting and in structuring transactions to alter financial reports to either mislead some stakeholders about the underlying economic performance of the company or to influence contractual outcomes that depend on reported accounting numbers" (p. 368).…”
Section: Real Earnings Managementmentioning
confidence: 99%
“…Earnings management, which is a key indicator of financial reporting quality (Ali and Kamardin, 2018) has become a major concern for the past two decades. The occurrence of financial scandals and the collapse of high profile companies as a result of financial reporting fraud have made earnings management a central issue to various stakeholders who massively use accounting information (Callao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This approach is most likely to happen when such expenses do not generate immediate income. Literature has documented that R&D spending is significantly less when the ability to report positive or increasing income in the current period is jeopardized (Gunny, 2015;Osma, 2008;Ali & Kamardin, 2018). Trejo-Pech et al (2015 found that firms reduce spending on R&D toward the end of their tenure to increase short-term earnings.…”
Section: Literature Reviewmentioning
confidence: 99%